Approach to English vocabulary learning by cadets of unspecialized High Schools (Pedagogy of Higher and Secondary Education, 2014)
Pryimachenko O. M. Approach to English vocabulary learning by cadets of unspecialized High Schools.The approach of unknown English vocabulary activation with the use of PowerPoint presentation is proposed in the article. Conceptual basics of the approach are substantiated, main methods of its realization are analized.
Keywords: English vocabulary activation; method of visualization; method of storytelling; image; context